Relationship, Transformation and Adaptation of The Traditionalists Against Puritanism in Surakarta Indonesia - Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
Surakarta is known as the center of Javanese culture with many traditions. On theother hand, this city also brings modern Islamic movements including the movementof the puritan group. The meeting of these two groups has created a unique relationbetween the supporters of the tradition of Java with the puritan group who is againstsuch tradition. This research uses a qualitative approach that aims to reveal therelation between the supporters of the Javanese tradition with puritan, transformationof the traditionalist group to be a puritan, the adaptation strategies of the supporterof Javanese tradition against puritan group who reject such tradition. This researchfound that despite there is dissociative relationship in terms of diversity, it does notlead to a direct physical conflict. Generally, the changing to be a puritan was affectedby social, educational and psychological process as well as rationalization of religioustradition. The strategy of the supporters of Javanese tradition to confront the puritangroup is by performing Javanese tradition both in the palace and their private space.They also conducted some activities hosted by a faith group in cooperation with atraditional Islamic group.